Asymmetric Synthesis of 3, 4, 6‐Trisubstituted 2, 5‐Diketopiperazines by Using Dynamic Kinetic Resolution of α‐Bromo Tertiary Acetamides. Issue 13 (6th March 2014) - Baek, Jinho; Kang, Seock Yong; Im, Chan; Park, Yong Sun
Abstract: A new and efficient method for the asymmetric synthesis of 3, 4, 6‐trisubstituted 2, 5‐diketopiperazines has been developed. The dynamic kinetic resolution ofL ‐amino‐acid‐derived α‐bromo tertiary amides in the nucleophilic substitution reaction with p ‐anisidine and a subsequent deprotection‐cyclization process provides rapid access to diverse cis ‐2, 5‐diketopiperazines5a –5o and proline‐containing trans ‐2, 5‐diketopiperazines5p –5t in enantiomerically pure form in 45–67 % overall yields. Abstract : A new asymmetric synthetic route to 3, 4, 6‐trisubstituted 2, 5‐diketopiperazines has been developed by using a nucleophilic substitution reaction ofL ‐amino‐acid‐derived α‐bromo tertiary acetamides with p ‐anisidine followed by a deprotection–cyclization process.